ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PELAYANAN KESEHATAN DI WILAYAH PESISIR - Susilawati Susilawati; Gustina Sari Siregar (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Coastal communities a group of people who are vulnerable to poverty because they are greatly influenced by weather conditions and seasons. The government plans to improve the welfare of fishing communities in the health sector by improving health services. Therefore, it is necessary to improve the healthy living habits of coastal communities by studying what factors influence the utilization of health services. problem of health service factors for coastal communities to see an overview of some of the existing health services. Five risk factors have been studied extensively in terms of factors affecting health services, namely demographics, social conditions, attitudes/beliefs, family income sources and resources